Medical Personality - A Concept In Medical Training. - Sateesh S.Jigjini (Al Ameen Medical College, 2009)
The dynamic and organized set of characteristics that uniquely influence the society are to be developed in the student. These traits play an important role as the doctor patient relation is a unique and sacred and bound by emotions of society. Therefore the medical teacher has to play a key role by exposing students to the community. A teacher has to identify his role in innovative courses with specific and less broad objectives.